2019
DOI: 10.1186/s12913-018-3822-2
|View full text |Cite
|
Sign up to set email alerts
|

Good governance, public health expenditures, urbanization and child undernutrition Nexus in Ethiopia: an ecological analysis

Abstract: BackgroundChild undernutrition remains the major public health problem in low and middle-income countries including Ethiopia. The effects of good governance, urbanization and public health expenditure on childhood undernutrition are not well studied in developing countries. The objective of the study is to examine the relationship between quality of governance, public health expenditures, urbanization and child undernutrition in Ethiopia.MethodsThis is pooled data analysis with ecological design. We obtained d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 19 publications
0
24
0
3
Order By: Relevance
“…Gupta et al [16] showed that the relationship between healthcare spending and mortality rates is weak. According to Biadgilign et al [18], there are no statistically significant relationships between public health spending and childhood undernutrition. Moreover, regarding the impact of the quantity of government, Bjørnskov et al [19] showed that a larger government reduces quality of life.…”
Section: Why Are the Quality And Quantity Of Government Important To mentioning
confidence: 99%
See 2 more Smart Citations
“…Gupta et al [16] showed that the relationship between healthcare spending and mortality rates is weak. According to Biadgilign et al [18], there are no statistically significant relationships between public health spending and childhood undernutrition. Moreover, regarding the impact of the quantity of government, Bjørnskov et al [19] showed that a larger government reduces quality of life.…”
Section: Why Are the Quality And Quantity Of Government Important To mentioning
confidence: 99%
“…Compared to complex discussion about the quality of government, the quantitative side of government is reduced to the public expenditure, which generally means the ratio of government spending on public health to total GDP. Gupta et al [16], Biadgilign et al [18], and Rajkumar and Swaroop [24] used the spending on public health as a proxy for quantity of government. Similarly, our study adopted the public expenditure as proxy for quantity of government.…”
Section: Literature Review: What Are Theoretical Issues In the Qualitmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that during political stability the government allocates more expenditure to healthcare and thus during periods of instability, it is inferred that the government can divert budget allocation away from healthcare expenditure to other non‐healthcare activities, which may include military expenditure. Recently, Biadgilign et al (2019) also find a strong and positive correlation between “political stability and absence of violence” and public healthcare expenditures in Ethiopia.…”
Section: Resultsmentioning
confidence: 95%
“…Most of the studies on determinants of healthcare expenditure have used demand function approaches to analyse the factors explaining healthcare expenditures, where healthcare expenditures are hypothesized to be a function of income (Newhouse, 1977) and a selection of non‐income variables such as population density (Crivelli et al, 2006; Hosoya, 2014), population's age structure (Barkat, Mrabet, & Alsamara, 2016; Okunade, Karakus, & Okeke, 2004), foreign aid (Barkat et al, 2016; Murthy & Okunade, 2009) and political stability (Biadgilign et al, 2019; Imoughele & Ismaila, 2013). While some models have applied either cross‐section regression (Murthy & Okunade, 2009) or time series regression (Tajudeen, Tajudeen, & Dauda, 2018), most studies have employed panel data models in both developed countries (Baltagi & Moscone, 2010; Murthy & Okunade, 2016) and developing countries (Barkat et al, 2016; Barkat, Sbia, & Maouchi, 2019; Lv & Zhu, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%